Acute Pediatric Pericarditis - Naif A. Alkhushi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Recognizing pericarditis in the emergency sitting is important, as it may be associated with life-threatening tamponade or myopericarditis. Typically children present with retrosternal chest pain and may appear ill. However in many instances the presentation is not typical and the management is delayed with serious consequences. Electrocardiogram may show typical signs of pericarditis and may suggest associated complications. Echocardiography is the modality of choice for its diagnosis and assessment. Suspected patients should be evaluated and managed by a pediatric cardiologist. The management may involve urgent pericardiocentesis or a surgically created pericardial window. Non-steroidal anti-infl ammatory drugs are the mainstay of medical treatment with some recent evidence supporting the value of using colchicine even in the first episode to prevent recurrence. Recurrence is an important and challenging concern requiring those children to have regular and careful follow up.